Variationin the useof angiography between procedural and non-procedural cardiologists - Zaichenko, Olga; Ahmed Yasin (My University, 2015)
Procedural cardiologists more often referred a patient with symptoms concerning for CAD directly for angiography compared to non-procedural cardiologists. When presented an abnormal stress test, both groups were equally likely to recommend angiography over additional stress testing. Therefore, clinical activities may influence management approaches; procedural cardiologists pursued an invasive approach earlier in the diagnostic pathway. Efforts to understand variation in invasive procedure use should take physician clinical activities into account.